The affective dimension of the ‘blacklivesmatter’ and ‘#metoo’ movements: socially situated events in the constitution of subjects - Estefogo, Francisco (The ESPecialist, 2025)
This article aims to explore the dimension of emotions and affects in the constitution of subjects and in linguistic communication, focusing on contemporary social upheavals. The centrality of emotions is evidenced in movements such as “#MeToo” and “BlackLivesMatter”, which somehow highlighted the impact of emotions on communicative practices and way of living. Theoretically, this proposal is grounded in the “affective turn” and the “pragmatic turn” of Applied Linguistics (Pennycook, 2001, 2006), as well as the importance of subjective experiences (Dilthey, 1978, 2002) and the philosophy of affects (Espinosa, 2009). The study examines how these theoretical and philosophical approaches can contribute to understanding the power of emotions in mobilizing groups and shaping collective identities, emphasizing the complexity of human language with respect to emotional communication as a crucial element for social transformation.